PERENCANAAN JALUR GANDA (DOUBLE TRACK) LINTASAN KERETA API PADA EMPLASEMEN STASIUN BOHARAN – STASIUN (KM 33+867 - KM 24+167) - Kevin Prawira; Nugroho Utomo (LPPM Universitas Abdurrab, 2025)
Trains are a mode of transportation with kinetic energy used to transport goods and people. The increasing demand for the use of train transportation makes the capacity of the railway track inadequate, because the existing conditions on the Boharan - Sepanjang track still use a single track. Thus, there is a plan for a double track railway on the Boharan - Sepanjang track to reduce the risk of accidents, delays in arrival and departure. In the planning of double track railways using the method of calculating the loading of the railway track, geometric planning of the railway track, calculation of the railway structure based on Service Regulation No. 10 of 1986 concerning Railway Construction Planning and Ministerial Regulation No. 60 of 2012 concerning Railway Track Techniques. The main focus of this study is to plan a double track railway track at the Boharan station - Sepanjang station (KM 33 + 867 - KM 24 + 167). In the double track structure of the railway in the Boharan plot - Throughout the review of this double track planning, the geometric planning of the railway track is divided into 2, namely horizontal alignment using SCS (Spiral-Circle-Spiral) type curves. The output of this study is to review the safety factor of dead load collapse on the railway structure, the safety factor of slope and lateral derailment against the reinforcement of the layer has met the requirements.